Legal problems and improving the activities of state bodies in the sphere of use and development of alternative energy sources (Journal of actual problems of jurisprudence, 2018)
The article considers theoretical and legal problems of improvement of activity of state bodies in the sphere of use and development of alternative energy sources. In connection with the development of renewable energy sources in the Republic of Kazakhstan , should be improvement the mechanism of the state regulation including the activities of state bodies. The aim of this work is to determine the legal status of state bodies in the sphere of use of alternative energy, development of proposals on improvement of their activities. On the basis of domestic and foreign experience to determine the model of the bodies for alternative sources of energy.In scientific work was used the methods of legal research as analysis, comparison, and heuristic method.Key words: alternative energy sources, renewable energy sources, ministry of energy, department for renewable energy sources, public administration, energy, energetic attitude.